2009
DOI: 10.4238/vol8-4gmr679
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic behavior of a nonaploid accession endorses x = 6 for Brachiaria humidicola (Poaceae)

Abstract: ABSTRACT. Brachiaria humidicola (Poaceae), originally from Africa, is an economically important pasture plant in tropical South America. An accession of B. humidicola (H038) collected from the wild African savanna (Mbeya, Tanzania) showed irregular microsporogenesis. This meiotic behavior was consistent with an allopolyploid origin. Multivalent chromosome association at diakinesis gave tri-to octavalents, associated with two nucleoli in some cells. Six non-congregated univalents in metaphase I and anaphase I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
(23 reference statements)
3
24
0
Order By: Relevance
“…Although the most frequent basic chromosome number in Urochloa is x = 9, other basic numbers, such as 6, 7, 8, and 10, have been reported for the genus (Basappa et al, 1987;Basavaiah, 1990;Morrone et al, 1995;Valle and Savidan, 1996;Risso-Pascotto et al, 2006). Polyploidy is also widespread in Urochloa and tetraploids are predominant, but other ploidy levels, such as 3, 5, 6, 8, 9, 10x, were also reported (Spies and Du Plessis, 1986;Basappa et al, 1987;Basavaiah, 1990;Nadeem Ahsan et al, 1994;Penteado et al, 2000;Boldrini et al, 2009). Variation in ploidy levels, together with reports of hybrids found in species of Urochloa (Risso-Pascotto et al, 2005;Mendes et al, 2006;Adamowski et al, 2008), suggest that events of reticulate evolution, as hybridization and/or allopolyploidization, could be common processes in the genus, generating potential incongruence between nuclear and plastid data (Linder and Rieseberg, 2004;McBreen and Lockhart, 2006).…”
Section: Clade IImentioning
confidence: 71%
“…Although the most frequent basic chromosome number in Urochloa is x = 9, other basic numbers, such as 6, 7, 8, and 10, have been reported for the genus (Basappa et al, 1987;Basavaiah, 1990;Morrone et al, 1995;Valle and Savidan, 1996;Risso-Pascotto et al, 2006). Polyploidy is also widespread in Urochloa and tetraploids are predominant, but other ploidy levels, such as 3, 5, 6, 8, 9, 10x, were also reported (Spies and Du Plessis, 1986;Basappa et al, 1987;Basavaiah, 1990;Nadeem Ahsan et al, 1994;Penteado et al, 2000;Boldrini et al, 2009). Variation in ploidy levels, together with reports of hybrids found in species of Urochloa (Risso-Pascotto et al, 2005;Mendes et al, 2006;Adamowski et al, 2008), suggest that events of reticulate evolution, as hybridization and/or allopolyploidization, could be common processes in the genus, generating potential incongruence between nuclear and plastid data (Linder and Rieseberg, 2004;McBreen and Lockhart, 2006).…”
Section: Clade IImentioning
confidence: 71%
“…1a) is also an evidence that both genomes are not closely related. Two nucleoli were also reported in several B. humidicola accessions with clear evidence of recent natural hybridization (Boldrini et al 2009(Boldrini et al , 2010. Other frequent meiotic abnormalities observed, with variable frequencies, were chromosome stickiness and the absence of cytokinesis.…”
Section: Resultsmentioning
confidence: 78%
“…In contrast, recent cytogenetic analyses in the germplasm collection of the B. humidicola/B. dictyoneura complex available at Embrapa beef cattle indicate that here the genomic chromosome number is x = 6 (Risso- Pascotto et al 2006a,b;Boldrini et al 2009Boldrini et al , 2010, making the species hexaploid and not tetraploid. Thus, the parents of the intraspecific hybrids discussed here (H031 and BRS Tupi) and their F 1 hybrids are hexaploids (2n = 6x = 36) and this is clearly demonstrated by the presence of hexavalents in diakinesis (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Recent cytogenetic studies have shown that this species is hexaploid and has a different base number (n=6) than the other three important Brachiaria species (n=9) (B. brizantha, B. decumbens and B. ruziziensis) (Boldrini et al 2009). In this case, the sexual plant found in nature has the same chromosome number as the main apomictic accessions.…”
Section: Genetic Resourcesmentioning
confidence: 97%